Haemoglobin polymorphism in different blood levels of Ethiopian Zebu x Holstein Friesian crossbred dairy cattle - Eyerusalem Tesfaye; Aberra Melesse; Simret Betsha; Dereje Andualem (PLoS ONE, 2026)
The present study aimed to investigate the biochemical polymorphism of haemoglobin (Hb) among three different blood levels (50%, 75%, and 87.5%) of Ethiopian Zebu x Holstein Friesian (HF) crosses at three milkshed locations by using horizontal agarose gel electrophoresis. To this effect, 117 crossbred lactating cows (39 cows per location namely Shashemene, Hawassa, and Dilla) were used. In each location, thirteen crossbred dairy cows were sampled from each blood level. The red blood cells were separated, washed and lysed following standard procedures. Then, the haemoglobin was typed using gel electrophoresis. The results indicated that the allelic frequencies of 0.89 and 0.11 for Hb A and Hb B , respectively. The corresponding genotype frequencies were 0.84, 0.11, and 0.05 for Hb AA , Hb AB , and Hb BB in the tested population, respectively. The Chi-square test revealed that the sampled population was not under Hardy-Weinberg equilibrium. The level of heterozygosity ranged from 0.03 in HF87.5% to 0.18 in HF50% in the studied milkshed dairy cows. The inbreeding coefficient (FIS) calculated for each subpopulation and then pooled across subpopulations, yielded values of 0.38 for blood-level groups and 0.41 for location-based groups, indicating substantial inbreeding within subpopulations. Although the Genetic differentiation (FST) value among subpopulations for blood level was numerically higher (0.06) than FST values for location (0.01), yet both estimates fall within the range typically interpreted as very low differentiation. In conclusion, the various genetic diversity measures and fixation indices revealed the existence of a reduced genetic diversity in the studied population at the biochemical level, which can be serve as foundational information to examine the breeding program for the crossbred dairy cattle in the studied milkshed.